Estudo e tratamento de conservação e restauro da pintura Feto do artista Jorge Pinheiro - Fernandes, Margarida dos Santos, 1992- (2016)
Followed by the opportunity of attending an internship at Argo – Art, Heritage and Culture, emerges the opportunity of studying and become responsible for the conservation and restoration of a painting by Jorge Pinheiro (Coimbra, 1931), whom is responsible for a wide artistic production that is vastly renowned and featured in particular and public collections, both nationally and internationally. This dissertation describes the study and the intervention of conservation and restoration of the contemporary painting Feto, executed in 1965 by Jorge Pinheiro, which was carried out during my internship of the Master’s in Science of Conservation, Restoration and Production of Contemporary Art, that took place in the company Argo, between November 2014 and April 2015. The issues in the conservation and restoration of contemporary art, related with the increasingly variety of materials that artists have been using since the beginning of the twentieth century, it’s also one of the main themes explored in this dissertation. From conservation and restoration, to the life and work of an artist, the following dissertation, besides describing in detail all the studies and steps that I took in the conservation and restoration of the oil on canvas painting, Feto (1965), it also reveals a closer look into the life and artistic career of Jorge Pinheiro